A STUDY ON STRESS AND TEACHING COMPETENCE OF SECONDARY SCHOOL TEACHERS IN AMROHA DISTRICT, U.P. - Tyagi, Priyanka; Singh, Aruna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the relationship between stress levels and teaching competence among secondary school teachers in Amroha District, Uttar Pradesh. The research aims to identify the factors contributing to teacher stress and its impact on their teaching effectiveness. A mixed-methods approach is employed, combining quantitative surveys and qualitative interviews with a sample of teachers. Quantitative data will be analyzed using statistical methods to examine correlations between stress indicators and perceived competence levels. The study anticipates contributing to educational psychology literature by highlighting the nuanced dynamics of teacher stress and competence in a specific regional context. Practical implications for teacher training and support programs are discussed to enhance well-being and instructional quality in secondary education settings.